Prevalence and Risk Factors of Depressive symptoms and Suicidal Behavior among Primary School Adolescents in Dar es Salaam, Tanzania (Tanzania Medical Journal, 2023)
Background                      Although Depression and suicide among adolescents have been studied in sub-Saharan Africa, there is a need to update the findings in Tanzania.It is essential to understand the magnitude of the depressive symptoms and suicidal behavior so that informed interventions can be undertaken regarding policy and program implications to save and improve the lives of young people. The study, therefore, aimed to determine the prevalence and factors associated with depressive symptoms and suicidal expression among adolescents.MethodsWe examined these questions using the Global School Health Surveillance (GSHS) database data. A total of 2176 students from Dar es Salaam schools were involved in the survey. A two-stage cluster sample design was used to produce data representative of all students in grades V to VI aged 11-16 years. A descriptive analysis summarized as frequencies and proportions was used to compute the characteristics of the respondents and the prevalence of depressive symptoms and suicidal expression. Age, sex, food insecurity, eating fruits or vegetables, education, substance use, exposure to bullying and/or violence, physical activities, and having supportive school or home environment were computed in logistic regression models to determine factors associated with the outcome of interest. Variables that reached 20%(p-value ≤0.2) under univariate analysis were further adjusted in a multivariable regression set at a statistical significance level of ≤0.05.ResultsThe study revealed that the prevalence of depressive symptoms and suicidal expression was 9.4% and 13.4%, respectively. Being of a male gender AOR:1.74 (95%CI:1.14, 2.65),p=0.0097, using alcohol AOR:2.33(95%CI:1.30, 4.19),p=0.0001, being a victim of bullying or physical attack AOR:3.58 (95%CI:2.40, 5.32),p=0.0001 and regularly going hungry AOR:2.24 (95%CI:1.46, 3.44),p=0.0002 significantly associated with depressive symptoms, while the overall use of tobacco AOR:1.87 (95%CI:1.08, 3.24),p=0.0261 and a history of depression predicted suicidal behavior AOR:2.99 (95%CI:1.92, 4.58),p=0.0001.ConclusionThe study reveals that depression and suicidal behaviors are common among teenagers and are a matter of public health importance. Further investigations in this subject area are crucial in addressing the problem.